"You could lose when you misuse" - factors affecting over-the-counter sale of antibiotics in community pharmacies in Saudi Arabia: a qualitative study - Faten Alhomoud; Reem Almahasnah; Farah Kais Alhomoud (BMC, 2018)
Abstract Background The sale of antibiotics without a prescription poses a global public health concern. Antibiotics dispensed without a prescription are largely recognised as a cause of antibiotic misuse and overuse which may result in antibiotic resistance, recurrent infection, increased cost and adverse effects of treatment. There have been no qualitative studies to explore the reasons for over-the-counter (OTC) sale of antibiotics, despite the fact that non-prescription sale of antibiotics are increasing in Saudi Arabia. Methods Qualitative interviews were conducted with community pharmacists living in the Eastern Province of Saudi Arabia using face-to-face, open-ended questions. Interviews were audio-recorded and transcribed verbatim. The interview transcripts were analysed using thematic analysis and NVivo 10 software. Results All participants declared that antibiotics were frequently sold without a medical prescription on an OTC basis. The main reasons for OTC sale of antibiotics were found to be related to the ease of access to community pharmacies compared to other healthcare services, expertise and knowledge of pharmacists and patients' trust, misconceptions and inappropriate practices of the public towards antibiotic use, customer pressure, pharmacists' need to ensure business survival and weak regulatory enforcement mechanism. These are presented in more detail below by using illustrative quotes from participants' transcripts. Conclusions The non-prescribed sale of antibiotics is still a common practice in Saudi Arabia, despite being a problem. The results of this study highlight the need to design interventions to promote rational use of antibiotics.